Adaptation of functional inspection test plan in a production line using a multi-agent system - Rodrigues, Nelson (2014)
The multi-agent systems technology is a proper approach to implement distributed manufacturing systems exhibiting adaptation and flexibility. This paper proposes a multi-agent based solution for the adaptation of the functional test plan in a production line producing washing machines, aiming to increase the process productivity and product quality. The global adaptation mechanism is embedded on the multiagent system infrastructure, allowing the optimized selection of tests based on the correlation of the quality data gathered along the production line. The proposed approach was developed and installed on a real production line producing washing machines under the European Seventh Framework Programme GRACE project.